Relasi Kekuasaan Masyarakat Aceh dalam Novel Tanah Surga Merah Karya Arafat Nur: Studi Kekuasaan Michel Foucault - Muhammad Hussen (Syntax Idea)
Tanah Surga Merah is one of the novels by Arafat Nur, the winner of the Jakarta Arts Council (Dewan Kesenian Jakarta-DKJ) novel competition in 2016. Previously, Arafat Nur has won a DKJ novel competition in 2010 through Lampuki's controversial novel which has reaped many blasphemies and also praise. Tanah Surga Merah was chosen as the object of research because it raised the issue of power that occurred in Nanggroe Aceh Darussalam. This research aims to reveal the various forms of power relations contained in the novel Tanah Surga Merah by Arafat Nur. What kinds of power relations appear in the novel? To reveal the power relations that appear in the novel, it will be used a study of power relations belonging to Michel Foucault. Novel Tanah Surga Merah by Arafat Nur work presents the power relations that happened to the people of Nanggroe Aceh Darussalam in 2014. These power relations work through media spread through religion, culture, country, institution, social body and individual body.